Media learning telegram bot - Rika Yulianti; Lilik sri Hariani; Udik Yudiono (Jurnal Riset Pendidikan Ekonomi, 2023)
This research was conducted with the aim of developing learning media based on Telegram Bot in subjects and to determine the feasibility of the media. This study uses the research and development (RnD) research method. This study adapts the ADDIE model along with the developed by Dick and Carry. The ADDIE research model consists of five stages, namely analysis, design, development, implementation, and evaluation.the meansurement scale used in this study is using a likert scale. The data obtained in this study used a validation assessment questionnaire by validators of media experts, linguists, and material experts. This research was declared feasible with the evidence of linguists expert validation results of 95%, media expert validation results of 85%, and material expert validation results of 79%. Thus, the developed learning media is declared feasible to use.